2018
DOI: 10.7150/thno.25156
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA-ZNF609 regulates retinal neurodegeneration by acting as miR-615 sponge

Abstract: Glaucoma is a major cause of visual impairment characterized by progressive retinal neurodegeneration. Circular RNAs are a class of endogenous noncoding RNAs that regulate gene expression in eukaryotes. In this study, we investigated the role of cZNF609 in retinal neurodegeneration induced by glaucoma.Methods: qRT-PCR and Sanger sequencing were conducted to detect cZNF609 expression pattern during retinal neurodegeneration. Immunofluorescence staining was conducted to detect the effect of cZNF609 silencing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 38 publications
(53 reference statements)
1
49
0
Order By: Relevance
“…This hypothesis was confirmed in the following, as the cytoprotective impacts of cZNF609 silence towards HaCaT cells were alleviated when miR-145 level was suppressed by the specific inhibitor. Previously, cZNF609 has been found to be the molecular sponges of a small fraction of miRNAs, such as miR-615 [33], miR-138-5p [17], miR-150-5p [34] and miR-145 [35]. Our findings agree with the previous observations.…”
Section: Discussionsupporting
confidence: 93%
“…This hypothesis was confirmed in the following, as the cytoprotective impacts of cZNF609 silence towards HaCaT cells were alleviated when miR-145 level was suppressed by the specific inhibitor. Previously, cZNF609 has been found to be the molecular sponges of a small fraction of miRNAs, such as miR-615 [33], miR-138-5p [17], miR-150-5p [34] and miR-145 [35]. Our findings agree with the previous observations.…”
Section: Discussionsupporting
confidence: 93%
“…In other words, ecircRNA formation was associated with alternative splicing in the linear mRNAs [51,55,114]. In addition, the expression of host genes and other genes could be regulated by circRNAs through sponging various miRNAs targeting different genes [115][116][117]. Furthermore, cir-cRNAs could bind to proteins to regulate the transcription of their locus genes.…”
Section: Regulation Of Transcription and Splicingmentioning
confidence: 99%
“…Wang et al revealed that cZNF609 is significantly upregulated in glaucoma-related retinal neurodegeneration. Retinal reactive gliosis and glial cell activation are inhibited by cZNF609 silencing ( Wang et al, 2018a ). They also found that cZRANB1 is potentially evolved in retinal degeneration induced by COH.…”
Section: Introductionmentioning
confidence: 99%